PERBANDINGAN SUMBER PAKAN DAN STRATEGI PEMBERIAN PAKAN Apis cerana DENGAN APIDAE LAINNYA: A REVIEW. - Rhavy Ferdyan; Ramadhan Sumarmin; Dwi Hilda Putri (Bio-Lectura : Jurnal Pendidikan Biologi, 2021)
Apis cerana, which is often known as honey bee, has spread from Afghanistan, China, Japan, to Indonesia. This distribution cannot be separated from Apis cerana's ability to survive by needing food. Pollen and nectar are the main food sources for Apis cerana in maintaining life. Apis cerana is widely cultivated by the community with its potential. This article aims to describe in more detail about the forage plants from Apis cerana and how the feeding strategies of honey bees were assembled from several studies in various regions, both in Indonesia and outside Indonesia as well as comparing these daily activities with other Apidae. The discussion is focused on the comparative analysis of the daily activities of Apis cerana with other Apidae to see the uniqueness of Apis cerana which is a factor in the number of bees being cultivated.